Implementation of safety performance framework (SPF) in process industries to avoid disasters - Shamim, M.Y. (Universiti Malaysia Pahang, 2018)
The reports of past major process disasters reveal that catastrophes are preventable and many of the problems are recognized prior to the accidents through the near-misses. The key element to improve safety performance is analyzing the performance indicators i.e. leading and lagging metrics in order to avoid process disasters. In past, the focus has only been given to the implementation of fourteen elements of process safety management (PSM) system, legislated under occupational safety and health administration (OSHA), for the effective safety system. However, it ignored the insight behaviour and performance of indicators along with its associated metrics for its every element. Therefore, to cater all these needs, a structured technique known as safety performance framework (SPF) has been suggested. It encompasses four major steps including a developed mathematical model i.e. safety performance index (SPI) to ensure the proper implementation of PSM in process industries. In addition to this, the identification of leading and lagging indicators for each PSM element is an integral part of this structure and is the real key to success. Moreover, this technique has been applied to the case studies of current process plant and the past disaster, where it has disclosed the insights of safety performance failure. Thus, SPF has been shown as a helpful tool to implement PSM in process industries to avoid disasters. Â© Universiti Malaysia Pahang, Malaysia.